2012
DOI: 10.1016/j.antiviral.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Novel antivirals inhibit early steps in HPV infection

Abstract: The future incidence of cervical cancer is forecast to decline because of the remarkably effective prophylactic vaccines against human papillomaviruses. However, lack of access to these expensive vaccines in the developing countries where cervical cancer is most frequent, and the restricted genotypes these vaccines protect against, will limit their impact. Clearly, there is still a need for identifying other modalities for preventing HPV infections. Ready access to effective, inexpensive antivirals represents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…When administered postattachment, this molecule directs virions into a noninfectious internalization pathway (12). A recent screen of a small-compound library has identified new antiviral molecules that inhibit a notyet-defined postentry step of HPV infection (42). In the same line, lately a genome-wide siRNA screen has identified the retromer as a cellular factor required for HPV infection and shown that Retro-2, a small molecule inhibitor of retrograde transport, inhibits HPV16 infection (43).…”
Section: Discussionmentioning
confidence: 96%
“…When administered postattachment, this molecule directs virions into a noninfectious internalization pathway (12). A recent screen of a small-compound library has identified new antiviral molecules that inhibit a notyet-defined postentry step of HPV infection (42). In the same line, lately a genome-wide siRNA screen has identified the retromer as a cellular factor required for HPV infection and shown that Retro-2, a small molecule inhibitor of retrograde transport, inhibits HPV16 infection (43).…”
Section: Discussionmentioning
confidence: 96%
“…Articles focusing on the following were excluded: condylomata acuminate, abnormal cytology, vaccine titers, genotyping, HPV biology only in females, HPV head and neck cancers, basic viral infection, proctology, and herpes simplex virus. Table 1 Burk et al, 2009;Da Costa et al, 2002;Day & Schelhaas, 2014;Doorbar et al, 2006;Duncan et al, 2015;Guiguet et al, 2009;Hessol et al, 2009;Joyce et al, 1999;Kajitani et al, 2012;Machalek et al, 2012;Matthews et al, 2003;Middleton et al, 2003;Morshed et al, 2014;Munger et al, 2004;Pokomandy et al, 2011;Pyeon et al, 2009;Roden et al, 2001;Schiller et al, 2010;Stanley et al, 2012;Strickler et al, 2005;Uronis & Bendell, 2007 Use of HTS for drug discovery Basu et al, 2011;Buck et al, 2006;Huang et al, 2012;Kumar et al, 2011;Mahida et al, 2013;Marin et al, 2015;Thompson et al, 2010 Note. HPV = human papilloma virus; HTS = high-throughput screening techniques.…”
Section: Methodsmentioning
confidence: 96%
“…However, there are several limitations to the vaccine. It is expensive, recommended to be administered between the ages of 9 and 26 years of age, and prior to sexual debut (Huang et al, 2012;Palefsky et al, 2011). The age and sexual debut restrictions on the administration of HPV vaccines create a gap in the continuum of care for anyone ages 26 years and older and anyone who has achieved sexual debut (Palefsky et al, 2011).…”
Section: A N U S C R I P Tmentioning
confidence: 98%
See 2 more Smart Citations